PRAT tool: a harmonization of antimicrobial stewardship program interventions - Marinei Campos Riccieri; Heloísa Barreto; Harli Pasquini-Netto; Lucas Okumura; Dandiany Sofka; Mariana Fachi; Fábio Motta (São Paulo State University (UNESP), 2021)
Objective: The Antimicrobial Stewardship Program (ASP) in hospitals aims to promote the rational use of antimicrobials, providing better results to patients (increasing effectiveness and decreasing the risk of adverse events), hospital epidemiology (impact on levels of microbial resistance), and enable cost-effectiveness studies. Therefore, a tool (called PRAT- antimicrobial therapy-related problem) is suggested in this paper. This unvalidated tool is the initial step towards organizing the antimicrobial therapy-related interventions to improve the use of this drug class, mainly by suggesting a harmonized registry process of ASP interventions. Methods: Therefore, this work presents the PRAT tool, developed based on the 10 years' experience of ASP at Pequeno Príncipe Hospital, inspired by the classification for drug-related problems of the Pharmaceutical Care Network Europe and according to a collaborative work using the Delphi technique. Results: This tool allows the identification and exact description of the antimicrobial therapy-related problem in 17 domains and 67 subcategories. Based on this identification, it suggests how to classify this problem (effectiveness, safety and need/indication) and what interventions can be conducted. Conclusion: This tool has the potential to establish a profile of antimicrobial-related problems, allowing prioritization to be visualized through the most (and least) interventions made in a given period, and might be useful in improving the quality of care through settings, by means of targeted educational interventions. Furthermore, if there is a harmonization of terminology for the classification of antimicrobial therapy-related problems, other hospitals can adopt it, and so the tool can improve research and comparison between institutions (benchmarking).